Development and Validation of a Miniature Programmable tDCS Device - Kouzani, Abbas Z.; Jaberzadeh, Shapour; Zoghi, Maryam; Usma, Clara; Parastarfeizabadi, Mahboubeh (IEEE transactions on neural systems and rehabilitation engineering, 2016)
Research is being conducted on the use of transcranial direct current stimulation (tDCS) for therapeutic effects, and also on the mechanisms through which such therapeutic effects are mediated. A bottleneck in the progress of the research has been the large size of the existing tDCS systems which prevents subjects from performing their daily activities. To help research into the principles, mechanisms, and benefits of tDCS, reduction of size and weight, improvement in simplicity and user friendliness, portability, and programmability of tDCS systems are vital. This paper presents a design for a low-cost, light-weight, programmable, and portable tDCS device. The device is head-mountable and can be concealed in a hat and worn on the head by the subject while receiving the stimulation. The strength of the direct current stimulation can be selected through a simple user interface. The device is constructed and its performance evaluated through bench and in vivo tests. The tests validated the operation of the device in inducing neuromodulatory changes in primary motor cortex, M1, through measuring excitability of dominant M1 of resting right first dorsal interosseus muscle by transcranial magnetic stimulation induced motor evoked potentials. It was observed that the tDCS device induced comparable neuromodulatory effects in M1 as the existing bulky tDCS systems.